Elastic-plastic halfspace simulation - Hauer, Franz; Willner, Kai (PAMM 2011, 2011)
Due to the roughness of technical surfaces only the surface peaks are in   contact for moderate contact pressures. Thus, the real contact area is smaller than the apparent contact area. Contact forces can only occur in the real contact area. Consequently it is necessary to determine the deformation of surface  asperities in order to analyse the tribological properties of surfaces. The real  contact area is usually small in initial contact. This leads to large contact  pressures which in turn lead to the plastic deformation of surface roughness  peaks. Therefore an elastic-plastic model is necessary. The halfspace model  seems to be beneficial because there is only a system of equations on a surface mesh to be solved and not on a volume mesh like in the Finite-Element-Method. This leads to a much smaller system of equations which should allow  reasonable calculation times even for large contact surfaces.
UnivIS-Import:2015-07-08:Pub.2011.tech.FT.FT-TM.elasti_5